Resor Air Terjun Pati Soni Di Kabupaten Kuantan Singingi Dengan Pendekatan Ekologi Arsitektur - Ayu Lastriani Putri; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pati Soni Waterfall located in the sub-district of Kuantan Mudik, Cengar village is one of the destination of the waterfall can be made as a natural tourism commodities of Kuantan Singingi. Lack of supporting facilities provided from both the government and the private sector make the Pati Soni Waterfalls could not attract tourists to visit and enjoy the natural tourism objects. Therefore there is a need for supporting facilities such as leisure facilities, shelter facilities and resort for tourists who can turn on the back and can be the attraction of tourists to come and enjoy the natural tourism objects Pati Soni Waterfalls. Methods in this design is to apply the principles of ecology architecture according to the theory of Heinz Frick (1998) into the building. The implementation of the principle of ecological building according to Heinz Frick (1998) into the Pati Soni waterfall Resort at Regency of Kuantan Singingi. The concept is transformation from nepenthes plant examination that applied to the building. In addition to the shape, orientation of Nepenthes plants leads to the river also applied to revival. Arrangement design of the Pati Soni Waterfall resort recreation area in Kuantan Singingi Regency with Ecological Architecture Approach produces a pattern of structuring the landscape and circulation spaces outside which follow the lines and contours of the pattern, so that the resulting view make recreational areas can attract visitors to come.Key word: Resort, Pati Soni, recreation facility, ecological architecture.